2008
DOI: 10.1063/1.2964680
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Entangled Polymeric Liquids through Simulations of the Primitive Chain Network Model with Finite Extensibility

Abstract: Articles you may be interested inNumerical simulation results of the nonlinear coefficient Q from FT-Rheology using a single mode pom-pom model J. Rheol. 57, 1 (2013); 10.1122/1.4754444 Statics, linear, and nonlinear dynamics of entangled polystyrene melts simulated through the primitive chain network model Transient and steady-state solutions of 2D viscoelastic nonisothermal simulation model of film casting process via finite element method Abstract. We here report on some modifications of the Primitive Chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Masubuchi et al [33] reproduce the probe rheology data reported by Matsumiya et al [30] using primitive chain network (PCN) model, which describes the dynamics of the network formed by the primitive chains and is used extensively in literature [34][35][36][37][38]. Their results agree with the experiment well.…”
Section: Introductionmentioning
confidence: 61%
“…Masubuchi et al [33] reproduce the probe rheology data reported by Matsumiya et al [30] using primitive chain network (PCN) model, which describes the dynamics of the network formed by the primitive chains and is used extensively in literature [34][35][36][37][38]. Their results agree with the experiment well.…”
Section: Introductionmentioning
confidence: 61%